Expanding Neonatal Bloodspot Screening: A Multi-Stakeholder Perspective - van Dijk, Tessa; Kater, Adriana; Jansen, Marleen; Dondorp, Wybo J.; Blom, Maartje; Kemp, Stephan; Langeveld, Mirjam; Cornel, Martina C.; van der Pal, Sylvia M.; Henneman, Lidewij (Frontiers in Pediatrics, 2021)
Neonatal bloodspot screening (NBS) aims to detect treatable disorders in newborns. The number of conditions included in the screening is expanding through technological and therapeutic developments, which can result in health gain for more newborns. NBS expansion, however, also poses healthcare, ethical and societal challenges. This qualitative study explores a multi-stakeholders’ perspective on current and future expansions of NBS. Semi-structured interviews were conducted with 22 Dutch professionals, including healthcare professionals, test developers and policy makers, and 17 parents of children with normal and abnormal NBS results. Addressed themes were 1) benefits and challenges of current expansion, 2) expectations regarding future developments, and 3) NBS acceptance and consent procedures. Overall, participants had a positive attitude towards NBS expansion, as long as it is aimed at detecting treatable disorders and achieving health gain. Concerns were raised regarding an increase in results of uncertain significance, diagnosing asymptomatic mothers, screening of subgroups (‘males only’), finding untreatable disorders, along with increasingly complex consent procedures. Regarding the scope of future NBS expansions, two types of stakeholder perspectives emerged. Stakeholders with a ‘targeted-scope’ perspective saw health gain for the neonate as the exclusive NBS aim. They thought pre-test information could be limited, and parents should be protected against too much options or information. Stakeholders with a ‘broad-scope’ perspective thought the NBS aim should be formulated broader, for example, also taking (reproductive) life planning into account. They put more emphasis on individual preferences and parental autonomy. Policy-makers should engage with both perspectives when making further decisions about NBS.